Card Match Circle Learning Media to Improve Science and Social Learning Outcomes - Widalaksita, Katrien; Dwi Prasetyaningtyas, Fitria (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Teachers have not included learning media in science learning, so students have difficulty learning. Based on this, this research aims to develop Card Match Circle Learning Media. This type of research is Research and Development (R&D) using ADDIE. This research used a small group of 6 subjects from fifth-grade elementary school students. The research subjects were 1 learning media expert and 1 learning materials expert.   The large group test participants for this research were 25 class V students. The methods used to collect data were interviews, observation, documentation and tests. The data collection instruments are in the form of questionnaires and test questions. The techniques used to analyze data are qualitative descriptive analysis, quantitative and inferential statistics. The research results, namely the feasibility test results, were obtained by 93.3% of media experts, and 92% of material experts who met the criteria were ready to be implemented. The t-test results show a fairly large difference in learning gains between the pretest and posttest scores of students in the small and large groups. The results of the N-gain test show that the increase in student learning outcomes is at medium criteria. It was concluded that the circle card match learning media on the diversity of Indonesian flora and fauna in class V was declared suitable for use and effective in improving the learning outcomes of science and science students in class V of elementary school. The research implication is that the media developed helps make it easier for students to learn.